Analisis Objek Vital, Pengamanan File, dan Pengamanan Cyber Pada PT. Krakatau Steel Cilegon - Edy Soesanto; Vina Hariyati; Munisari Munisari; Navia Naveli (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
Acts of theft at PT Krakatau Steel Cilegon can negatively affect the company's production and operations. Theft activities can also threaten industry sustainability, disrupt supply chains, and affect price stability. So that it can create security vulnerabilities, both in terms of strategic information, as well as in maintaining the security of physical facilities and employees. Cases of theft of national vital objects have increased in recent years. Theft can be committed by internal or external parties, including employees, contractors, or other parties. The motivation for theft can be varied, ranging from gaining profit, to obtaining sensitive information. File security and cyber security need to be carried out by the company PT Krakatau Steel Cilegon to handle cases of theft of the company's physical assets.